Differences in the Immune Microenvironment of Anal Cancer Precursors by HIV Status and Association With Ablation Outcomes. (2nd September 2017) - Liu, Yuxin; Gaisa, Michael M; Wang, Xiaofei; Swartz, Talia H; Arens, Yotam; Dresser, Karen A; Sigel, Carlie; Sigel, Keith
Abstract : Human papilloma virus–associated anal dysplastic lesions are prevalent in human immunodeficiency virus (HIV)–infected persons. In this study we compare patterns of lymphocytic infiltration in high-grade anal dysplastic lesions by HIV status and in association with treatment outcomes. Abstract: Background: Anal high-grade squamous intraepithelial lesions (HSILs) are the precursors to anal cancer and frequently persist or recur following electrocautery ablation (EA). Impaired mucosal immunity may facilitate anal carcinogenesis. We characterized the immune microenvironment of anal HSILs in correlation with human immunodeficiency virus (HIV) serostatus and ablation outcomes. Methods: Using immunohistochemistry, mucosa-infiltrating CD4 + and CD8 + lymphocytes were quantified in HSILs and benign mucosa from 70 HIV+ and 45 HIV− patients. Clinicopathological parameters were compared. Results: Anal HSILs harbored more T lymphocytes than benign mucosa regardless of HIV status ( P ≤ .03). Total T lymphocyte count and CD8 + subset were significantly higher in HIV+ HSILs versus HIV− HSILs (median cell count, 71 vs 47; 47 vs 22/high power field [HPF]; P < .001), whereas the CD4 + subset was comparable between groups (median, 24 vs. 25; P = .40). Post EA, HSILs persisted in 41% of HIV+ and 19% of HIV− patients ( P = .04). Unadjusted analysis showed trends toward EA failures associated with HIV seropositivity (incidence rate ratio [IRR], 2.0; 95% CI, .8–4.9) and increased CD8 + cells (IRR, 2.3; 95% CI, .9–5.3). Conclusions: . Human immunodeficiency virus is associated with alterations of the immune microenvironment of anal HSILs manifested by increased local lymphocytic infiltrates, predominately CD8 + . Human immunodeficiency virus seropositivity and excess mucosa-infiltrating CD8 + cells may be associated with ablation resistance.